From isotopes to ice: Constraining SW Gondwana ice sources via detrital zircon geochronology during the LPIA - Griffis, Neil (2016)
The late Paleozoic Ice Age (LPIA) is the longest lived and geographically most extensive glacial interval of the Phanerozoic Era, and the only time a metazoan dominated and vegetated world transitioned from an icehouse into a greenhouse climate. Despite widespread efforts, our ability to constrain the relative timing, scale and magnitude of the LPIA is largely precluded by a lack of radioisotopic age control for high latitude glacial deposits, fragile reconstructions of ice centers and ice dynamics through the glaciation, which ultimately prohibits the reconstruction of ice volume. Recent high resolution CATIMS analysis of zircon restricts the waning to the latest Carboniferous-Permian Boundary in the Paraná Basin. In the Tepuel Basin, a similar time period of waning is inferred from the youngest detrital zircons measured using less precise LAICPMS ages. Here we present >500 detrital zircon UPb analyses from the stratigraphically lower and uppermost glacial deposits of two key LPIA archives, the Paraná and Tepuel basins. Detrital zircons from diamictites are used to fingerprint sedimentary provenance, and thus constrain ice centers and investigate ice dynamics though the LPIA glaciation. Preliminary field and geochemical observations suggest a more proximal ice source in the lowermost portion of the sedimentary succession in both basins. The zircon analyses from the lower portion of the sections delineate a geochemical signature that strongly reflects local provenance and dilutes components of a distal sediment source. The uppermost units in both basins suggest a glacial waning that is reflected in a decrease of proximal ice indicators and relative increase in distal sediment sources. The UPb ages of the Paraná Basin glacial diamictites suggest agreement with Namibian bedrock ages likely confirming an SW African ice center. In the Tepuel basin the UPb and Hf isotopes match well with the Desado Massif of SE Patagonia as well as Antarctica and S Africa.